2016
DOI: 10.1161/strokeaha.116.014413
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Preliminary Efficacy of Early Tirofiban Treatment After Alteplase in Acute Ischemic Stroke Patients

Abstract: URL: http://www.chictr.org.cn/. Unique identifier: ChiCTR-TRC-14004630.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 11 publications
5
66
0
Order By: Relevance
“…In these retrospective studies, tirofiban displayed adjuvant benefits in reperfusion, with relatively low risk of intracranial hemorrhage, and about 50% patients achieved favorable outcomes thanks to adjuvant tirofiban infusion. Moreover, Li et al (25) had demonstrated the safety and efficacy in a prospective study. Nonetheless, Kellert et al (26) cautioned about the risk of fatal intracerebral hemorrhage and poor outcome associated with tirofiban in endovascular stroke therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In these retrospective studies, tirofiban displayed adjuvant benefits in reperfusion, with relatively low risk of intracranial hemorrhage, and about 50% patients achieved favorable outcomes thanks to adjuvant tirofiban infusion. Moreover, Li et al (25) had demonstrated the safety and efficacy in a prospective study. Nonetheless, Kellert et al (26) cautioned about the risk of fatal intracerebral hemorrhage and poor outcome associated with tirofiban in endovascular stroke therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Abciximab, the glycoprotein IIb/IIIa inhibitor, has an irreversible action on platelets, whilst other inhibitors, such as tirofiban and eptifibatide, have a reversible action and may reduce periprocedural hemorrhagic complications [28]. A recent open-label non-randomized study found that hemorrhagic complications did not increase in acute stroke patients who undertook 3 days of intravenous tirofiban infusion immediately following intravenous tissue plasminogen activator, compared to patients who were given intravenous tissue plasminogen activator only [29]. The use of glycoprotein IIb/IIIa inhibitors appears to be potential safe and effective treatment, although further randomized clinical trials are needed to confirm their efficacy.…”
Section: Therapeutic Strategy For Acute Icas-omentioning
confidence: 99%
“…The progression occured on average 27.85 hours (6-72 hours) after the onset of stroke symptoms. The average NIHSS score at hour 1 of admission was 7.14 (2-6); the score at the time of progression occurence was 10.21 (5-21) with an average NIHSS increase of 3.07 (2-11); at 24 hours after administration of tirofiban, the score was 9.79 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and on discharge the score was 9.46 (1-18) (Figure 1). In the evaluation of the patient groups in terms of stroke subtypes, the NIHSS score was found to be highest in the cardioembolic stroke group and lowest in the small vessel disease group.…”
Section: Resultsmentioning
confidence: 99%
“…An evaluating preliminary study that included two patient groups which received Tirofiban + alteplase or only alteplase treatment has reported that when study group received tirofiban + alteplase treatment was compared to the study group which received only alteplase treatment, safe, feasible and potentially efficacious with improved outcomes were observed in study group which received tirofiban + alteplase treatment (11). In an another study which compared Tirofiban monotherapy, trombolytic treatment and interventional treatment, bleeding complication was not observed in tirofiban group but recanalization rate was found lowly (25%) compared to other groups (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation